2018
DOI: 10.1186/s12887-018-1190-z
|View full text |Cite
|
Sign up to set email alerts
|

SPORTS STARS study protocol: a randomised, controlled trial of the effectiveness of a physiotherapist-led modified sport intervention for ambulant school-aged children with cerebral palsy

Abstract: BackgroundModified sport interventions run by physiotherapists have shown potential as cost-effective, engaging, and effective interventions to improve gross motor skills and support transition to real-world sports participation for children with cerebral palsy. At present, this population demonstrates decreased participation in physical activities and sport compared to peers due to barriers ranging from body function to accessibility challenges. Sport provides culturally relevant opportunities for social inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 64 publications
(61 reference statements)
1
36
0
5
Order By: Relevance
“…This can be explained by the fact that, when young, this patient performed activities that may develop strength in the body and, therefore, part of his muscular strength was preserved. This is in line with the literature, where it has been reported that resistance exercise from childhood is beneficial in preventing muscle loss as the individual ages, making it an important strategy for maintaining and increasing muscular mass and strength [18,19].…”
Section: Discussionsupporting
confidence: 90%
“…This can be explained by the fact that, when young, this patient performed activities that may develop strength in the body and, therefore, part of his muscular strength was preserved. This is in line with the literature, where it has been reported that resistance exercise from childhood is beneficial in preventing muscle loss as the individual ages, making it an important strategy for maintaining and increasing muscular mass and strength [18,19].…”
Section: Discussionsupporting
confidence: 90%
“…Some authors did not reference palsy typography, referring only to CP [ 12 , 13 , 14 , 15 , 16 , 17 ]. From the other studies, 12 focused on spastic hemiplegia/paresis, 9 focused on spastic diplegia/paresis, 7 on just spastic CP, 7 investigated unilateral and bilateral spastic CP and 2 studies included subjects with all types of CP [ 18 , 19 ]. The participants were also classified according to the Gross Motor Function Classification System (GMFCS).…”
Section: Resultsmentioning
confidence: 99%
“…A few authors investigated areas such as manual therapy [ 53 ], respiratory physical therapy [ 54 ], and alternative therapies [ 55 ]. Finally, [ 16 ] analyzed the effect of segmental training in gross motor function, whereas [ 19 ] focused their attention on sports-specific fundamental movement skills training.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations